(untitled) (Bangladesh Heart Journal, 2024)
Background: Clinically significant depression is estimated to occur in a significant portion of chronic heart failure (CHF) patients and increases sharply with increase in heart failure severity. However, the frequency and predictors of depression in this group of patients are underreported. This study was designed to assess frequency & predictors of depression in patients of chronic heart failure with reduced ejection fraction (HFrEF). Methods: This cross-sectional analytical study was performed in the department of Cardiology, Dhaka Medical College Hospital, Dhaka, during the period from October’2018 to Septemeber’2019. One hundred and fifty-two CHF patients with reduced ejection fraction (<40%) either admitted in the department of Cardiology or attended Cardiology OPD, Dhaka Medical College Hospital (DMCH), Dhaka who fulfilled the selection criteria were included into the study. A translated and validated Patient Health Questionnaire (PHQ-9) in Bengali was used to assess depression level in CHF patients in this study. Informed written consent was taken from each patient. Approval for the study was taken from Ethical Review Committee (ERC) of Dhaka Medical College before commencement of the study. After compiling data from all participants, statistical analyses were performed using the Statistical Package for Social Science (SPSS), version 22.0 for windows. Results: Mean age of the patients was 58.68±9.40 years, ranging from 36 to 75 years. Male predominance was noted (72% vs 28%). Overall, frequency of depression was 56%. Among the depressed patients (n=85), majority (40%) had minimal depression while 27%, 19% and 14% had mild, moderate and severe depression. respectively. Among the different risk factors, DM and sedentary lifestyle were significantly associated with depression (p<0.05). Age >65 years, sedentary lifestyle, and H/O past MI were independently associated with depression among chronic HErEF patients. Widowed patients, diabetes, hospital readmission in last 2 months before study inclusion and NYHA class III/IV were also significantly associated with depression among patients with chronic HFrEF (p<0.05). Conclusion: More than half of the patients with chronic HFrEF had concurrent depression of varied severity. Proper care of depression along with HF may improve the survival and quality of life of these patients. Bangladesh Heart Journal 2024; 39(2): 74–84